Euro Area House Prices and Unconventional Monetary Policy Surprises - Oliver Hülsewig; Horst Rottmann (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper examines the reaction of house prices in a panel of euro area countries to monetary policy surprises over the period 2010-2019. Using Jordà's (2005) local projection method, we find that real house prices rise in response to expansionary monetary policy shocks that can be related to unconventional policy measures. In the core countries including Ireland, we also find that lending for house purchases increases relative to nominal output. Thus, household debt rises.
Keywords: E52; E58; E32; G21; 330; Euro area house prices; unconventional monetary policy; local projection method